Question

If in the expression of (1 + x)m (1 – x)n. the coefficient of x and x2 are 3 and – 6 respectively, then m is

Solution

Correct option is

12

m(m – 1) + n(n – 1) – 2mn = – 12

or (m – n)2 – (m + n) = – 12

or 9 – (2m – 3) = – 12    ∴ m = 12

SIMILAR QUESTIONS

Q1

The digit at unit place in the number 171995 + 111995 – 71995 is

Q2

If the sum of the coefficients in the expression of (1 + 2x)n is 6561. The greatest term in the expression at x = 1/2 is

Q3

The number of terms in the expression of (a + b + c)n, where n Ïµ N, is

Q4

The number of terms which are free from fractional powers in the expansion of (a1/5 + b2/3)45a ≠ b is

Q5

If n is an odd natural, then  equals

Q6
Q7

The coefficient of xm in (1 + x)r + (1 + x)r+1 + (1 + x)r+2 +….+ (1 + x)nr≤ m ≤ n is

Q8

 respect to x, is

Q9

 is a polynomial of degree 5, then n

Q10

The number of terms in (1 + x)101 (1 + x2 – x)100 is